Turquía. Potencial aliado en la creciente inserción de Colombia en la economía global (2013)
Turkey is strategically located between Asia and Europe, what makes it interesting is its level of awareness in the face of this situation, since its inhabitants have realized, over time, the value of their territory and the advantages it offers , making him an important player in international affairs. It is characterized by being a secular country, where government decisions are independent of the moral preaching of the Islamic religion, both politically and in education. In the last decade, Turkey has been showing significant growth in its economy, (Businessmonitor, 2013) becoming an attractive country for direct foreign investment and also an important commercial ally for different countries, including Colombia. The degree of influence that Turkey has acquired over the years becomes crucial when making decisions in both regional and global geopolitics, given that it has the approval and support of nations as important as some European states and countries. United States of America, being a great ally for these nations and having a decision system, in a high percentage isolated from religious fundamentalisms. He presents himself to the world as an important player in diplomatic matters concerning the Middle East. Thanks to the above, it is interesting to carry out an analytical and reflective approach, about the role that Turkey plays, as a potential ally for Colombian commercial expansion and its idea of ​​penetrating different markets, thus diversifying its investments and exports.